Intercultural Education in Catalonia (Spain): Evolution of Discourses and Practices (2000-2016) - Jordi Garreta-Bochaca; Monica Macia-Bordalba; Núria Llevot-Calvet (Universidad de Navarra, 2020)
This paper analyses the evolution of intercultural discourses and practices in Catalan schools (Spain), based on two studies contextualised in different times. The first study was conducted in the 2000/2001 academic year, a time of incipient immigration and the incorporation of the intercultural discourse. The second study (2015/2016), nevertheless, took place in a context of migratory stabilisation and consolidation of the intercultural discourse in the autonomous community. Both studies took the quantitative methodological approach. The results showed that intercultural discourses and practices have evolved positively (in terms of their presence in school documents, actions taken and teacher training) and in keeping with European Union guidelines over the years. However, it still remains the challenge of debunking the belief that intercultural education is related to students of foreign nationality, and therefore the practice that intercultural education is mainly addressed at schools with high percentages of students of foreign nationality.